2008
DOI: 10.1038/bmt.2008.243
|View full text |Cite
|
Sign up to set email alerts
|

BM-derived cells randomly contribute to neoplastic and non-neoplastic epithelial tissues at low rates

Abstract: Epithelial cancers can arise from BM-derived cells (BMCs) in animal models. We studied whether the same phenomenon can occur in humans. Biopsy specimens from carcinomas and healthy adjacent tissues were obtained from three women who had undergone allogeneic BMT from an HLA-matched brother. Complete donor hematopoietic chimerism was verified by cytogenetic analysis, RFLP analysis or by reverse transcription-PCR analysis. Biopsies were studied for the presence of the Y chromosome derived from BM-derived cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Other groups have suggested that microchimerism might contribute to the development of neoplastic epithelial tissues [18,19]. However, this remains unresolved as there are also data arguing against the possibility that BMDSCs represent a direct source of carcinomas in the recipients [20]. There are reports of better BMDSC donor cell engraftment at sites with injury, such as lung after radiation [6], GI inflammation [21], and skin blistering [16].…”
Section: Resultsmentioning
confidence: 99%
“…Other groups have suggested that microchimerism might contribute to the development of neoplastic epithelial tissues [18,19]. However, this remains unresolved as there are also data arguing against the possibility that BMDSCs represent a direct source of carcinomas in the recipients [20]. There are reports of better BMDSC donor cell engraftment at sites with injury, such as lung after radiation [6], GI inflammation [21], and skin blistering [16].…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Moreover, evidence on the interaction between hematopoietic donor and host epithelial cells in stem cell transplantation might lead to a potential benefit of HSCT in certain epithelial disorders. [14][15][16] TTC7A-deficient patients with associated immunodeficiency may therefore benefit from HSCT; however, the effect of engrafted donor cells on chronic intestinal inflammation and gut epithelial tissue regeneration is unknown. 14,15 Follow-up data on HSCT in TTC7A deficiency are required to understand the impact of this treatment on the disease phenotype and to guide the management of future cases.…”
mentioning
confidence: 99%
“…[14][15][16] TTC7A-deficient patients with associated immunodeficiency may therefore benefit from HSCT; however, the effect of engrafted donor cells on chronic intestinal inflammation and gut epithelial tissue regeneration is unknown. 14,15 Follow-up data on HSCT in TTC7A deficiency are required to understand the impact of this treatment on the disease phenotype and to guide the management of future cases. In this study, we report the clinical and histological evolution of 4 TTC7A-deficient patients who are alive 19 to 114 months post-HSCT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conjecture about the cell origin of the non-hematopoietic tissues after HSCT has led to a closely related theory that cancer could also be donor-derived. So far, the evidence of this hypothesis is extremely scarce and only further systematic searches for donor-derived stem cells in the newly diagnosed solid tumor in long-term survivors after HSCT will shed some light on this controversial theory (Houghton et al, 2004;Alison et al, 2006;Arai et al, 2006;Avital et al, 2007;Soldini et al, 2008).…”
Section: Cancer Originating From Donor Hscmentioning
confidence: 99%